2008
DOI: 10.1007/s11033-008-9220-9
|View full text |Cite
|
Sign up to set email alerts
|

Borealin is differentially expressed in ES cells and is essential for the early development of embryonic cells

Abstract: Maintaining undifferentiated state and self-renewal ability of embryonic stem cells is a process that many genes and factors participate in. Using bioinformatics analyses and suppression subtractive hybridization we cloned a novel human gene related to the proliferation of human embryonic stem (hES) cells and its mouse homologue and identified them as being borealin. Our data demonstrated that borealin was highly expressed in undifferentiated ES cells, mouse pre-implantation embryos and the brain of 8.5-9.5 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Four of the six cycling mitosis genes were over-detected on both 8-Cell and hES arrays relative to fibroblasts: CDCA8 (borealin), ESPL1 (separase), FBX05 (Emi1) and TPX2. Borealin is a chromosomal passenger protein required for stability of the bipolar mitotic spindle [37] and recently reported to be essential for cleavage from the 2-cell to 4-cell stage of mouse embryos [38]; separase cleaves cohesin to allow the separation of sister chromatids [39] and cleaves the linker between mother and daughter centrioles to license centriole duplication [40]; Emi1 represses APC/C cdh1 in G2 [36], thus blocking the degradation of Cyclin A, -B and geminin, and allowing both the formation of new DNA replication initiation sites and the prevention of re-replication of DNA before mitosis. Emi1 is essential for mouse embryo development beyond the blastocyst stage [41] and for normal development in zebrafish [42].…”
Section: Resultsmentioning
confidence: 99%
“…Four of the six cycling mitosis genes were over-detected on both 8-Cell and hES arrays relative to fibroblasts: CDCA8 (borealin), ESPL1 (separase), FBX05 (Emi1) and TPX2. Borealin is a chromosomal passenger protein required for stability of the bipolar mitotic spindle [37] and recently reported to be essential for cleavage from the 2-cell to 4-cell stage of mouse embryos [38]; separase cleaves cohesin to allow the separation of sister chromatids [39] and cleaves the linker between mother and daughter centrioles to license centriole duplication [40]; Emi1 represses APC/C cdh1 in G2 [36], thus blocking the degradation of Cyclin A, -B and geminin, and allowing both the formation of new DNA replication initiation sites and the prevention of re-replication of DNA before mitosis. Emi1 is essential for mouse embryo development beyond the blastocyst stage [41] and for normal development in zebrafish [42].…”
Section: Resultsmentioning
confidence: 99%
“…Microinjection of anti-Borealin (encoded by CDCA8) antibody into mouse zygotes arrested development at the 2-4-cell stage (16). These results indicate that CDCA8 may play a crucial role in hESCs and early embryonic development.…”
mentioning
confidence: 83%
“…We previously showed that CDCA8 is highly expressed in undifferentiated human ES cells (hESCs) and early mouse embryos but is expressed at low levels in differentiated hESCs (dhESCs) (15,16). Microinjection of anti-Borealin (encoded by CDCA8) antibody into mouse zygotes arrested development at the 2-4-cell stage (16).…”
mentioning
confidence: 99%
“…The results are also consistent with previous work in human mitosis (10) and in mouse embryo. (25) The most important roles of the CPC are the regulation of the spindle assembly checkpoint and of chromosomal alignment. (26,27) Our previous work also showed that survivin is involved in the regulation of the spindle checkpoint in mouse oocyte meiosis (19).…”
Section: Discussionmentioning
confidence: 99%